Migrant Family Trajectories and Contributions to the Host Society: Interdisciplinary and International Reflections - Lardoux, Solène; Flahaux, Marie-Laurence; Mondain, Nathalie; Dogba, Maman Joyce; Meintel, Deirdre (Enfances, Familles, Générations)

(untitled) (INRS-UCS, 2023)
Research framework: Although immigrants participate in many domains of the host society, their integration may prove difficult, for some time after their arrival. Objectives : This issue aims to provide a better understanding of the trajectories of migrant families and their contributions to the societies to which they belong. It aims to give an account of adaptation and integration strategies based on pre- and post-migration histories, through the prism of the family. Methodology: The methods come from a variety of disciplinary fields, including sociology, anthropology, social and transcultural psychiatry, literature, psychology, social work and history. The various qualitative approaches mainly concern family and individual trajectories, as well as intergenerational trajectories, in different societies. Results: Family transformations result from factors linked to the family's pre-migration past, but also from the characteristics of the society where migrants arrive, including the bureaucracy surrounding migration and settlement, the services provided (or not provided) to migrant families, non-recognition of qualifications and work experience, discrimination, and so on. These aspects that are "external" to the family can condition relationships, well-being and the quality of life within the family. Conclusion : Migration transforms families who arrive or that are formed in host countries. Their integration and participation in host societies and the links maintained with the country of origin are influenced by a series of individual, family, societal and global factors. In particular, parental migration can have significant consequences on the well-being of children who may have experienced trauma and anxiety arising from difficult situations along the way. Contribution : Using a multidisciplinary, qualitative approach, the authors demonstrate the importance of documenting family issues associated with migration. The complexity of migrants' journeys, their resilience and their ability to adapt to the host society described in this issue bear witness to the urgent need to work towards better recognition of their skills, simplify administrative procedures and facilitate their access to healthcare.